Avian influenza overview April – June 2023 - European Food Safety Authority, European Centre for Disease Prevention and Control, European Union Reference Laboratory for Avian Influenza; Cornelia Adlhoch; Alice Fusaro; José L Gonzales; Thijs Kuiken; Angeliki Melidou; Gražina Mirinavičiūtė; Éric Niqueux; Karl Ståhl; Christoph Staubach; Calogero Terregino; Francesca Baldinelli; et al. (EFSA Journal)
Abstract Between 29 April and 23 June 2023, highly pathogenic avian influenza (HPAI) A(H5N1) virus (clade 2.3.4.4b) outbreaks were reported in domestic (98) and wild (634) birds across 25 countries in Europe. A cluster of outbreaks in mulard ducks for foie gras production was concentrated in Southwest France, whereas the overall A(H5N1) situation in poultry in Europe and worldwide has eased. In wild birds, black‐headed gulls and several new seabird species, mostly gulls and terns (e.g. sandwich terns), were heavily affected, with increased mortality being observed in both adults and juveniles after hatching. Compared to the same period last year, dead seabirds have been increasingly found inland and not only along European coastlines. As regards mammals, A(H5N1) virus was identified in 24 domestic cats and one caracal in Poland between 10 and 30 June 2023. Affected animals showed neurological and respiratory signs, sometimes mortality, and were widely scattered across nine voivodeships in the country. All cases are genetically closely related and identified viruses cluster with viruses detected in poultry (since October 2022, but now only sporadic) and wild birds (December 2022–January 2023) in the past. Uncertainties still exist around their possible source of infection, with no feline‐to‐feline or feline‐to‐human transmission reported so far. Since 10 May 2023 and as of 4 July 2023, two A(H5N1) clade 2.3.4.4b virus detections in humans were reported from the United Kingdom, and two A(H9N2) and one A(H5N6) human infections in China. In addition, one person infected with A(H3N8) in China has died. The risk of infection with currently circulating avian H5 influenza viruses of clade 2.3.4.4b in Europe remains low for the general population in the EU/EEA, low to moderate for occupationally or otherwise exposed people to infected birds or mammals (wild or domesticated).